Estrategias de mediación para reducir la violencia en los estudiantes de bachillerato del colegio particular Dr. José María Vivar Castro periodo 2023-2024 - Coronel López, Sheila Denisse (2024)
The aim of this research work was to analyse the mediation strategies to reduce violence in high school students at the public school Dr. José María Vivar Castro in the city of Loja, presenting as a final result an intervention manual to mitigate violence within the educational centre. The research allowed us to observe whether violence occurs within the institution between students, teachers and administrative staff, which from a theoretical and epistemological research provided us with valuable information that was supported on the basis of a qualitative study. For this purpose, an interview was carried out with the school's teachers and high school students, as well as an observation sheet that provided us with valuable information that allowed us to construct a peer violence prevention manual based on an integral approach, due to the results obtained, These intervention strategies were created in a playful way so that teachers, students and parents can get involved. They also fulfil the function of using mediation and conflict resolution strategies to ensure that the institution manages quality standards for an adequate education free of violence. Finally, the research fulfilled the proposed objectives by analysing the educational institution, creating intervention strategies and presenting the manual to prevent violence in the institution of study with the commitment to apply and use the various strategies presented during the next school year to prevent peer violence and creating new and innovative ways to reduce violence within the institution.